Coronavirus: Where Has All the Health Economics Gone? - Cam Donaldson; Craig Mitton (Kerman University of Medical Sciences, 2020)
As the coronavirus disease 2019 (COVID-19) pandemic continues to unfold there is an untold number of trade-offs being made in every country around the globe. The experience in the United Kingdom and Canada to date has not seen much uptake of health economics methods. We provide some thoughts on how this could take place, specifically in three areas. Firstly, this can involve understanding the impact of lockdown policies on national productivity. Secondly, there is great importance in studying trade-offs with respect to enhancing health system capacity and the impact of the mix of private-public financing. Finally, there are key trade-offs that will continue to be made both in terms of access to testing and ventilators which would benefit greatly from economic appraisal. In short, health economics could - and we would argue most certainly should - play a much more prominent role in policy-making as it relates to the current as well as future pandemics.